Introduction of Information Technology at TMA Split with the Purpose of Optimisation and ... - Markežić, Ivan; Kosor, Denis; Roguljić, Slavko (Promet - Traffic&Transportation, 2012)
The introduction of information technology into the Croatianair traffic control system at the TMA Split and the applicationof computer programs have significantly improved airtraffic safety. In other words, a reliable and fast analysis is providedas well as remote control of technical systems, reductionof possible human errors in pre-flight and in-flight activities.Also the preconditions are created for its integration into thecomputer sysrems of other air traffic participants.